54th AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2013
DOI: 10.2514/6.2013-1748
|View full text |Cite
|
Sign up to set email alerts
|

The Smart Normal Constraint Method for Directly Generating a Smart Pareto Set

Abstract: In design situations where a single solution must be selected, it is often desirable to present the designer with a smart Pareto set of solutions-a minimal set of nondominated solutions that sufficiently represents the tradeoff characteristics of the design space.These sets are generally created by finding many well-distributed solutions and then either filtering out the excess ones or searching more closely in those regions that appear to have significant tradeoff. Such methods suffer from the inherent ineffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…The authors showed that this improved on the NNC method's ability to generate a more uniformly distributed Pareto frontier. This idea was recently taken further by Hancock and Mattson (2013), developing the smart normal constraint (SNC) method. Additional linear constraints, known as smart constraints (Haddock et al (2008)), are used to determine which approximate point is most likely to produce a smart Pareto solution.…”
Section: Normal Constraint Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors showed that this improved on the NNC method's ability to generate a more uniformly distributed Pareto frontier. This idea was recently taken further by Hancock and Mattson (2013), developing the smart normal constraint (SNC) method. Additional linear constraints, known as smart constraints (Haddock et al (2008)), are used to determine which approximate point is most likely to produce a smart Pareto solution.…”
Section: Normal Constraint Methodsmentioning
confidence: 99%
“…The authors show that the SNC method alleviates the need for a Pareto filter to generate smart Pareto sets. This improves the computational expense of the algorithm, since the Pareto filter first generates many solutions, then reduces the set by removing solutions that are considered insignificantly different from other Pareto points (Hancock and Mattson (2013)). Such an approach is computationally inefficient as a large number of designs, which are later removed from consideration, are generated.…”
Section: Normal Constraint Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this context, the use of Pareto set does not require a previous articulation of preferences. Many methods have been created with the intent of abbreviating the set of Pareto solutions [13]. The ''knee method'' [14] is a posteriori method that identifies the points for which an improvement in one objective results in a significant worsening of at least one other objective.…”
Section: Introductionmentioning
confidence: 99%